TLR4 ASP299GLY (RS4986790) AND THE PREDISPOSITION TO GRAM-NEGATIVE GALLBLADDER EMPYEMA IN ACUTE CALCULOUS CHOLECYSTITIS: A PROSPECTIVE-RETROSPECTIVE COHORT STUDY (European Journal of Interdisciplinary Research and Development, 2026)
Gallbladder empyema, the bacterially infected and pus-filled form of acute cholecystitis, carries a conversion rate to open surgery that is three to four times higher than for gangrenous cholecystitis alone and is the single strongest predictor of systemic sepsis in this disease. The innate immune receptor TLR4 governs the first-line cellular response to gram-negative lipopolysaccharide, and its Asp299Gly missense variant (rs4986790) reduces signal transduction efficiency. Whether this functional hyporesponsiveness translates into a clinically recognisable predisposition to empyema in a real-world surgical cohort has not been studied.